Imaging the node-linker coordination in the bulk and local structures of metal-organic frameworks - Boyuan Shen (Nature Portfolio, 2020)
Metal-organic frameworks (MOFs) are so sensitive to electron beams that it is challenging to atomically image their structures by electron microscopy. Here, the authors use the integrated differential phase contrast technique in STEM to achieve the low-dose imaging of a beam-sensitive MOF, revealing its detailed local structure.